Physical properties of rocks fundamentals and principles of petrophysics - Schon J H (Amsterdam Elsevier, 2004)
The book is a comprehensive and concise systematic presentation of the physical properties of rocks. It is focussed on the problems of applied geophysics with respect to exploration and the expanding field of applications in engineering and mining geophy
Keywords: Petrology; Petrophysics; Rocks; Rocks-properties